Shear behavior of RC pile cap beams strengthened using ultra-high performance concrete reinforced with steel mesh fabric. (December 2022) - Fayed, Sabry; Badr el-din, Ahmed; Basha, Ali; Mansour, Walid
Abstract: Although pile cap bases of structures are the most significant element in the construction and one of the most difficult parts in strengthening applications, previous studies on this element, particularly strengthening, are quite limited. The most extensively utilized, highly efficient, and simple to implement solution is ultra-high performance concrete (UHPC). In this study, six-half scaled pile cap beams were prepared and experimentally tested. Three of them were strengthened with UHPC (one in shear with connectors only, one in shear with connectors and steel mesh fabric (SMF), and one in shear and punching with connectors and SMF), while the other three were not strengthened to explore the influence of side bars. The bottom bars of the all six beams were identical, consisting of main longitudinal tensile and secondary lateral reinforcement. The load-displacement response, ultimate carrying load, failure mechanisms, energy dissipation capacity, and shear ductility of pile cap beams were all thoroughly investigated. The results revealed that using side bar reinforcement and UHPC with various techniques significantly enhanced the shear strength and ductility of pile cap beams. Except for the specimen including additional internal side bars, there were no appreciable differences in the peak load of un-strengthened reinforced concrete (RC) pile cap beams. The gain in peak load was 59% due to use of side bars. The RC pile cap beam strengthened in shear and punching with connectors and SMF exhibited the highest peak load and the highest energy dissipation capacity among all tested specimens.